Offshoring and Wage Inequality: Theory and Evidence from China - Liugang Sheng; Dennis T. Yang (Institute of Labor Economics (IZA), 2017)
We present a global production sharing model that integrates the organizational choices of offshoring into the determination of relative wages in developing countries. The model shows that offshoring through foreign direct investment contributes more prominently than arm's length outsourcing to the demand for skill in the South, thereby increasing the relative wage of skilled workers. We incorporate these theoretical results into an augmented Mincer earnings function and test the model based on a natural experiment in which China lifted its restrictions on foreign ownership for multinational companies upon its accession to the World Trade Organization in 2001. Empirical findings based on detailed Urban Household Surveys and trade data from Chinese customs provide support to our proposed theory, thus shedding light on the changes in firm ownership structure, the skill upgrading in exports, and the evolution of wage inequality from 1992 to 2008 in China's manufacturing sector.
Keywords: F16; J31; D23; 330; offshoring; ownership structure; processing trade; wage inequality; China